2020
DOI: 10.3390/ijms21217914
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria Residing at Root Canals Can Induce Cell Proliferation and Alter the Mechanical Properties of Gingival and Cancer Cells

Abstract: Understanding the importance of oral microbiota in human health and disease also leads to an expansion of the knowledge on functional, metabolic, and molecular alterations directly contributing to oral and systemic pathologies. To date, a compelling number of studies have documented the crucial role of some oral cavity-occurring microbes in the initiation and progression of cancers. Although this effect was noted primarily for Fusobacterium spp., the potential impact of other oral microbes is also worthy of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 82 publications
1
10
0
Order By: Relevance
“…The mechanical changes were accompanied by the alterations in the internal structure of the actin cytoskeleton. Changes in the structure of cells and changes in the cell stiffness under the influence of pathogens were also observed in other studies [ 51 , 52 , 53 ]. The study [ 52 ] presents the results where human gastric neoplastic cells were treated with the tumor necrosis factor-inducing protein α (TNF-α) Tipα produced by H. pylori , which determines the protein as a carcinogen in the gastric epithelium.…”
Section: Discussionsupporting
confidence: 77%
“…The mechanical changes were accompanied by the alterations in the internal structure of the actin cytoskeleton. Changes in the structure of cells and changes in the cell stiffness under the influence of pathogens were also observed in other studies [ 51 , 52 , 53 ]. The study [ 52 ] presents the results where human gastric neoplastic cells were treated with the tumor necrosis factor-inducing protein α (TNF-α) Tipα produced by H. pylori , which determines the protein as a carcinogen in the gastric epithelium.…”
Section: Discussionsupporting
confidence: 77%
“…Suprewicz et al assessed the effect of P.acnes on the proliferation capability and mechanical features of gingival cells and cell lines derived from breast, lung, and ovarian cancer. It was observed that P. acnes had the highest growth-promoting abilities in relation to breast cancer MCF-7 and ovarian cancer SKOV-3 cells [ 59 ]. These studies suggest that P. acnes may be crucial agent for the development of cancer diseases.…”
Section: P Acnes May Also Contribute To Other Cancers and In...mentioning
confidence: 99%
“…Biofilms that are formed on dental fillings can destroy the structure of the filling components, which results in a rougher surface of the material [ 10 ], and rough surfaces are more susceptible to colonization [ 10 , 11 ]. Bacteria can penetrate between the filling components and the tooth structure [ 12 ], which may cause secondary caries [ 13 ] and pulp inflammation. During maturation of the biofilm, microbes are metabolically active, and they use endogenous components from saliva to form an extracellular matrix that helps with co-adhesion [ 14 ].…”
Section: Introductionmentioning
confidence: 99%